This Book is Irregular: On the critical-creative nexus. (Consciousness, Literature & the Arts (1573-2193), 2013)
Chapter 1 of the book "Reading Coetzee" is presented. It highlights the 1984 essay of novelist J. M. Coetzee on writing and the concept of middle voice along with its role as a critical-creative nexus model. It also outlines his criticism as well as the ideas of French author Maurice Blanchot on ambiguity and the conception of literary critic Matei Calinescu on re-reading.